2023
DOI: 10.1017/s0950268823000213
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of quadrivalent HPV vaccination in reducing vaccine-type and nonvaccine-type high risk HPV infection

Abstract: This study aimed to assess human papillomavirus (HPV) vaccine effectiveness (VE) against both vaccine-type and nonvaccine-type high-risk HPV (hrHPV) infection, and duration of protection in United States. The study population was female participants aged 18–35 years with an HPV vaccination history and genital testing for HPV from the National Health and Nutrition Examination Survey, 2007–2016. Participants vaccinated before sexual debut were assessed against 13 nonvaccine-type hrHPV infection including 31/33/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Similar dramatic declines in hepatocellular carcinoma incidence have been observed after initiation of HBV newborn vaccination programs globally from Gambia to Thailand. These data clearly demonstrate the population-level cancer prevention benefits achievable when effective viral vaccines are administered early and broadly to intercept oncogenic infection [19].…”
Section: Efficacy In Preventing Cancer By Blocking Infectionmentioning
confidence: 65%
“…Similar dramatic declines in hepatocellular carcinoma incidence have been observed after initiation of HBV newborn vaccination programs globally from Gambia to Thailand. These data clearly demonstrate the population-level cancer prevention benefits achievable when effective viral vaccines are administered early and broadly to intercept oncogenic infection [19].…”
Section: Efficacy In Preventing Cancer By Blocking Infectionmentioning
confidence: 65%
“…It is also critical to check genotypes not targeted by the HPV vaccine. Li C et al reported a prevalence of high-risk non-vaccine types of 25.4% and a prevalence of vaccine types of 9.3% [28] among females aged 18-35 who received the 4vHPV vaccine, based on self-collected cervicovaginal samples. In a recent study [14], it was noted that although HPV-51 is not included in the 9vHPV vaccine, its prevalence has been decreasing, along with HPV 31, 33, and 39 over the last decade in Taiwan.…”
Section: Discussionmentioning
confidence: 99%